Endoscopic lung volume reduction with endobronchial valves in patients with severe emphysema and established pulmonary hypertension - Eberhardt, Ralf; Gerovasili, Vasiliki; Kontogianni, Konstantina; Gompelmann, Daniela; Benjamin, Nicola; Herth, Felix; Grünig, Ekkehard; Nagel, Christian (Respiration, 2015)
Background: One of the most common forms of pulmonary hypertension (PH) is that associated with chronic obstructive pulmonary disease (COPD). So far, patients with severe emphysema and established PH have been excluded from endoscopic lung volume reduction (ELVR) therapy due to the risk of right heart decompensation. Objective: The aim of this pilot study was to evaluate the feasibility and efficacy of ELVR using one-way endobronchial valves (EBV) in this specific group of patients. Methods: We prospectively included 6 patients with COPD, severe heterogeneous emphysema, and established PH who underwent right heart catheterization and clinical assessments before and 90 days after ELVR with unilateral EBV placement. Results: This study was not powered to measure any statistical differences in endpoints. Ninety days after ELVR, the symptoms, lung function, and hemodynamics improved in 5 out of 6 patients (1 patient normalized and 1 slightly worsened). The mean hemodynamics improved from baseline to 90 days after ELVR as follows: mean pulmonary artery pressure, -2.5 ± 3.5 mm Hg; pulmonary arterial wedge pressure, -4.3 ± 8.3 mm Hg; cardiac index, +0.3 ± 0.6 l/min/m2, and 6-min walk distance, +59 ± 99 m. ELVR was performed without PH-related complications in all patients. Conclusion: To our knowledge, this is the first prospective, single-center pilot study to evaluate the feasibility and efficacy of ELVR in patients with established PH. ELVR was feasible and resulted in an improvement of clinical and hemodynamic parameters in 5 out of 6 patients. These results have to be further confirmed in larger-scale controlled studies.